Utilização do planejamento fatorial completo aplicado ao estudo das propriedades térmicas dos nanocompósitos PMMA-co-PMPTS/ MMT H+ - Santana, Joseane de Andrade (2015)
Since the first report from the Toyota research group, polymer/clay nanocomposites have attracted great interest and lots of attempts to prepare these nanocomposites. The addition of small contents of clay into polymer matrix exhibits potential increase in the physical and chemical properties such as flame retardance, barrier, flame and solvent resistances, thermal properties and advanced corrosion coatings. The study of polymer/clay nanocomposites are of fundamental importance due to a better understanding of the structural properties which optimizes its applications. The morphology of these nanocomposites depends on strongly of the synthesis conditions such as clay content and the synthetic method. Therefore, the use of the multivariable systems (factorial design of experiments) to evaluate the effect of experimental variables on the properties of the nanocomposites is of great relevance. In the present study, nanocomposites obtained from copolymerization of poly(methyl methacrylate), PMMA and poly(methacryloxy propryltrimethoxysilane), PMPTS forming PMMA-co-PMPTS and adding protonate montmorillonite (MMT H+) clay were prepared via in situ polymerization using benzoyl peroxide (BPO) as thermal initiator. Factorial design systems (four factors at two levels) were used to study the influence on effects of experimental variables (MMA, MPTS, MMT H+ and BPO) on the thermal properties of (PMMA-co-PMPTS)/MMT H+ nanocomposites using thermogravimetry. The structure and morphology were studied by X-ray diffraction, fourier transform infrared and transmission electronic microscopy. The study of thermal properties through the factorial design showed that the sample prepared by combining 150 mmol of MMA, 23 mmol MPTS, 0.186 mmol BPO and 0.150 g MMT H + (experiment 7, AM7) showed the highest depolymerization temperature (Td) (381 ° C). The value of the determination coefficient (R2) obtained by the statistical model indicated that the mathematical model of the first order explained 96.11% of the variability of Td and the correlation of predicted versus observed values was considered very strong, which presented a value of 0.9818. Along with the structural and morphological study it was possible to identify the partial compatibility between PMMA and MMT H +.